The Parla-CLARIN Recommendations for Encoding Corpora of Parliamentary Proceedings - Tomaž Erjavec; Andrej Pančur (Journal of the Text Encoding Initiative)
Parliamentary proceedings are a rich source of data that can be used by scholars in various humanities and social sciences disciplines. Unlike the sources of most other language corpora, parliamentary proceedings are not subject to copyright or personal privacy protections, and are typically available online, thus making them ideal for compilation into corpora and for open distribution. For these reasons many countries have already produced corpora of parliamentary proceedings, but each typically in their own encoding, limiting their comparability and utilization in a multilingual setting. In this paper we propose an encoding schema which could serve as an interchange format for parliamentary corpora compiled for the purposes of scholarly investigations. The schema, called Parla-CLARIN, was developed within the CLARIN research infrastructure, and is written as a TEI ODD which includes a TEI customization and prose guidelines with examples of use. We discuss the coverage and choices made in designing the recommendations, and give an overview of the guidelines. We also discuss two other standard schemas for encoding parliamentary data, Akoma Ntoso and RDF, and their relation to Parla-CLARIN. We conclude by presenting corpora already encoded in Parla-CLARIN and discussing further work, especially the provision of a set of example documents and of transformation scripts that would make the proposed encoding more usable.